Health Risks Faced by Turkish Agricultural Workers - Hülya Çakmur (The Scientific World Journal)
Background. Individuals who make a living through agriculture and animal husbandry are faced with a variety of physical and psychological health risks. In many international studies, it has been shown that these risks can result in disease. The purpose of this study is to summarize the health risks faced by Turkish agricultural workers. Materials and Methods. This study used a nonrandom, convenience sample. The biopsychosocial health statuses of 177 farmers from 11 central villages in Kars, Turkey, were examined. Results. It was determined that the depression rate among the study group was 62.1%, the rate of physical health problems was 52.0%, and the rate of social isolation was 53.7%. There was a statistically significant difference between the depression scale scores and lower education levels, having ≥ three children, and physical health problems, as well as the physical condition of the farmers’ homes. There was a significant difference between poor physical health and older age, lower education levels, having ≥ three children, and social isolation. Conclusions. In providing data-based evidence, it is believed that this study will contribute considerably to understanding the causality of health problems in this population and in planning the development of public health and veterinary services based on regional needs.